Instructional Leadership in the Age of AI: Guiding Effective Use of AI Tools in University English Speaking Practice - Ping He; Aida Hanim A Hamid; Mohamed Yusoff Mohd Nor (PT Mattawang Mediatama Solution, 2025)
The fast-evolving artificial intelligence (AI) has revolutionized the higher sectors of education particularly the messaging segments of English speaking. The opportunities brought by AI tools include chatbots, speech recognition, and 24/7 virtual tutoring that are all available at more individual utilized levels with direct feedback, though need to be supported by a strong leadership in instruction to be effective. The systematic review (SLR) of literature applied in this paper as the PRISMA technique to cover the role of leadership to enhance the contribution to adoption and integration of AI tools in the English-speaking practice at the university level. The review identified three main themes that should be factored in to inform how AI should be used in the academic world. The outcomes indicate that a successful implementation factor occurs because of the well-considered strategy in a leadership domain, teacher training and materials, and organizational integrity and inclusion policies. The results indicate that AI implementation is a non-technological problem but an initiative of the executives who have to implement such strategies as tactical thinking, groupwork, and the ethical duty to improve the performance of language learning even further.